Використання портретів людини в рекламі, як психологічний метод впливу на споживача - Ніконова, А. (My University, 2020)
Original appearance of advertisement substantially influences how our brain perceives a product. Advertisers, noticing it, began to use psychological tricks. One of them is the usage of people`s portraits that encourages a customer to change their attitude towards the goods they buy
Keywords: портрет; реклама; психологічний метод; споживач